Dampak Program Keluarga Harapan dalam Pengentasan Kemiskinan di Desa Bangga Kecamatan Paguyaman Pantai - Latare, Sainudin; Harold, Rudy; Bumulo, Sahrain; Ali, Ahmad (Dynamics of Rural Society Journal, 2023)
The Family Hope Program (PKH) is a social assistance program that is provided to help poor families in rural areas. According to the Regulation of the Minister of Social Affairs of the Republic of Indonesia Number 1 of 2018 concerning the Family Hope Program, it is explained that "to improve the quality of life of poor and vulnerable families through increasing accessibility to health, education and social welfare services. This research aims to analyze the impact of the PKH program in alleviating poverty in rural communities. Research using qualitative methods with a descriptive approach. The results showed that the PKH program had a major impact on poor families in Bangga Village, where many PKH beneficiary communities benefited from the program. Even though the assistance funds received by the community are not large, the existence of the PKH program has lightened the burden on the community in meeting their daily needs, including the basic needs of poor households, the need to get education services, health services, and other needs of poor households.